2018
DOI: 10.1175/jamc-d-17-0121.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of the WRF Model: Wind-Resource Assessment for Complex Terrain

Abstract: Wind energy requires accurate forecasts for adequate integration into the electric grid system. In addition, global atmospheric models are not able to simulate local winds in complex terrain, where wind farms are sometimes placed. For this reason, the use of mesoscale models is vital for estimating wind speed at wind turbine hub height. In this regard, the Weather Research and Forecasting (WRF) Model allows a user to apply different initial and boundary conditions as well as physical parameterizations. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 56 publications
4
53
1
Order By: Relevance
“…For instance, the YSU scheme was observed to generally predict higher wind speeds than the MYNN3 scheme due the relatively shallower mixed layer that it simulates [2,3,21]. PBL schemes were found to have more significant impacts on error metrics of surface wind speed hindcasts than other parameterization schemes in studies in similarly coastal terrains [2,22]. Furthermore, the often relatively better ranking of the MYNN3 PBL scheme (over the other local closure schemes) is possible due to it being of a higher order closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the YSU scheme was observed to generally predict higher wind speeds than the MYNN3 scheme due the relatively shallower mixed layer that it simulates [2,3,21]. PBL schemes were found to have more significant impacts on error metrics of surface wind speed hindcasts than other parameterization schemes in studies in similarly coastal terrains [2,22]. Furthermore, the often relatively better ranking of the MYNN3 PBL scheme (over the other local closure schemes) is possible due to it being of a higher order closure.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in the tropics [17][18][19][20][21] have often not tested the different PBL schemes with different compatible SL schemes. In addition, the impact of the schemes on model performance is influenced by local terrain features and atmospheric conditions, which often vary with geographical location [2,3]. Against this background, in this paper, we investigate the impact of selected PBL schemes, paired with several compatible SL schemes, on wind hindcasts for wind energy assessment purposes in an area in coastal Ghana.…”
Section: Planetary Boundary and Surface Layer Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, wind field simulation over complex terrain is an important topic for consideration in the atmospheric science field. Traditionally, mesoscale models, such as the Fifth-Generation Penn State/National Center for Atmospheric Research Mesoscale Model (MM5), Regional Atmospheric Modelling System (RAMS), and Weather Research and Forecasting (WRF), are important tools in predicting the wind field over complex terrain [1][2][3][4][5][6][7][8]. However, a terrain-following coordinate system and smoothing processes for terrain data are applied to deal with the complex terrain in most mesoscale…”
Section: Introductionmentioning
confidence: 99%
“…Fernández‐González et al . () concluded that the WRF model could simulate wind flow realistically in complex terrain when high‐resolution grid spacing was used. However, they emphasized the importance of conducting sensitivity analyses to find the best initial and boundary conditions and the best combination of physical parametrizations to produce the best simulations in different environments.…”
Section: Model Description and Experimental Setupmentioning
confidence: 99%